Wafer-scale synthesis of a uniform film of few-layer MoS2 on GaN for 2D heterojunction ultraviolet photodetector. (8th August 2018) - Goel, Neeraj; Kumar, Rahul; Roul, Basanta; Kumar, Mahesh; Krupanidhi, S B
Abstract: Layered transition metal dichalcogenide materials grown over a conventional 3D semiconductor substrate have ignited a spark of interest in the electronics industry. The integration of these 2D layered materials extensively addresses the formidable challenges faced by a new generation of opto-electronic and photovoltaic devices. Herein, we have demonstrated a 2D/3D heterojunction type photodetector by depositing MoS2 on a GaN substrate with a mass-scalable sputtering method. Spectroscopic and microscopic characterizations expose the signature of the highly crystalline, homogeneous and controlled growth of a deposited few-layer MoS2 film. The greater light absorption of few-layer MoS2 results in the high performance of the MoS2 /GaN photodetector. Our device shows high external spectral responsivity ( 10 3 A W −1 ) and detectivity ( 10 11 Jones) with a very fast response time ( 5 ms). Our obtained results are significantly better than previous MoS2 - and GaN-based photodetectors. This work unveils a new perspective in MoS2 /GaN heterojunctions for high-performance optoelectronic applications.